Testing of some nitro compounds as new plasticizers of polymeric membrane-based electrodes - Vytřas, Karel; Kadeřábková, Milena; Socha, Jaromír (Univerzita Pardubice, 1997)
An ion-pair formation-based titration monitored by simple polymeric membrane-containing electrodes of the coated-wire type proved as a procedure suitable for quick testing of new plasticizers. In the titration of a model compound, extraction capabilities of individual plasticizers can be estimated from the magnitude of the potentiometric titration break. A proper amount of a plasticizer needed for preparation of the membrane can be evaluated graphically as a maximum value of this break. However, the lifetime of the membranes must also be taken into account. From the 15 nitro compounds under test, all 2,4-dinitrophenyl n-octyl, 2-nitrophenyl n-octyl and 2-nitrophenyl 2-ethylhexyl ethers proved to be the most suitable from both the criteria (the lifetime of the sensing electrode as well as the value of the potential break). Dialkyl 3-nitrophthalates can also be recommended giving the titration breaks equivalent to those obtained with 2-nitrophenyl alkyl ethers. With other nitro compounds tested, either the potential break is sharp enough but the lifetime of corresponding sensors is more or less shortened, or the break magnitude is depressed.